Characteristics and Effectiveness of Blended Learning Through Reality Laboratory and Virtual Laboratory Activities in Genetics Course - Abdu Mas'ud; Sundari Sundari; Intan Fitriani Azahraa (Universitas Veteran Bangun Nusantara Sukoharjo, 2022)
Virtual laboratories can provide real learning experiences through computer-aided simulations and activities. Virtual laboratory is rapidly developing its use in science learning because it is proven to provide significant benefits to the process and results of science learning during the pandemic. The limitations of laboratory facilities in genetics learning at the unkhair Biology Education Study program have encouraged the development of virtual practicum strategies and their use in genetic learning with modified free inquiry strategies on the topic of the structure and function of genetic material and reproduction of genetic material. The purpose of this study was to analyze the effectiveness of virtual laboratories based on student perceptions of the use of virtual laboratory applications and to describe and compare these perceptions with the use of laboratory reality and relevant previous research results. There are five aspects of perception surveyed, namely innovation, motivation, effectiveness, benefits, and presentation of practical procedures. This research method uses a quasi-experimental research design for the characteristics and effectiveness of using virtual laboratories and real laboratories in the Genetics course at the Biology Education Study Program, Khairun University, Ternate on the topic of DNA isolation, chromosomes and mitosis. The results of this study indicate that: the characteristics of Blended Learning practicum in the Genetics course in 4th semester students of Biology study program are: 1) instruction-based practicum; 2) practicum based on data collection and reporting of practicum results; 3) practicum based on proof of concept. The effectiveness of the implementation of genetics practicum in laboratory reality and virtual laboratories based on the perception of student responses is more likely to choose reality laboratories than virtual laboratories. The effectiveness of the implementation of genetic practicum based on the results of the practicum report is known to be not significantly different between the results of the practicum in reality and in the virtual laboratory.